Regional redistribution: Applying data from household income data - Nirmala Ravishankar (Luxembourg Income Study (LIS), 2003)
This paper evaluates the use of microeconomic data, namely household income surveys from the Luxembourg Income Study (LIS), for researching interregional redistribution. Patters of regional growth and regional redistribution are the focus of a growing body of literature. Most of these studies use macroecomomic indicators like real GDP to estimate per capita income. LIS survey data offers researchers the opportunity to construct estimates of regional income distribution and interregional redistribution based on household income information for over 25 countries. The goal of this paper is to present a preliminary analysis of interregional inequality and redistribution in four federal states - the United States of America, Canada, Germany and Australia, using LIS data. Firstly, it estimates interregional inequality based on household income before and after redistribution. In the first method, interregional redistribution is defined as the percentage reduction in interregional inequality from before taxes and transfers to after and calculated by comparing the 'between-group' Theil Index before and after redistribution. In the second method, a simple regression model is used to estimate the effect of pre-redistribution mean income in a region on its post-redistribution mean income after controlling for population. The format of the paper is as follows. Section II offers a brief overview of the literature focusing on the key theoretical arguments that have framed the study of interregional redistribution. Section III provides a description of the LIS household income data and a discussion of research methodology. The empirical results from the data analysis are presented in Section IV. Finally, Section V sums up the main findings of this paper and explores ways to expand this research in the future.
Keywords: 330; Regionale Disparität; Nationaleinkommen; Räumliche Verteilung; USA; Kanada; Australien; Deutschland